Prematurity, Subclinical Intraamniotic Infection, and Fetal Biophysical Parameters: Is There a Correlation?. Issue 2 (1993) - Cox, Susan M.; Roberts, Scott; Roussis, Percilis; Campbell, Berry A.; Curry, Thomas E.
Abstract : Objective: This prospective study was undertaken to examine the effects of subclinical intraamniotic infection on fetal behavioral patterns. Methods: Amniotic fluid was obtained from four groups of patients (n = 99): group 1, patients with preterm premature rupture of the fetal membranes (PPROM) without infection; group 2, patients with PPROM and infection; group 3, patients with preterm labor (PTL) and without infection; and group 4, patients with PTL and infection. Fetal biophysical profiles were obtained on admission to the labor suite. Amniotic fluid was analyzed for the presence of microorganisms and endotoxin to confirm intraamniotic infection; cytokines interleukin (IL)-1β, IL-6, and IL-8 were also assayed. Results: We found no association between low scores for biophysical parameters and subclinical infection in patients with PPROM or PTL. Conclusions: We could not demonstrate that upon a patient's admission to the labor hall absent fetal breathing and absent fetal movement, as well as reactivity, correlate with subclinical intraamniotic infection. Elevated cytokines, i.e. IL-1β, IL-6, and IL-8 were associated with subclinical chorioamnionitis.